2020
DOI: 10.3390/app10010412
|View full text |Cite
|
Sign up to set email alerts
|

A Bio-Inspired Flapping Wing Rotor of Variant Frequency Driven by Ultrasonic Motor

Abstract: By combining the flapping and rotary motion, a bio-inspired flapping wing rotor (FWR) is a unique kinematics of motion. It can produce a significantly greater aerodynamic lift and efficiency than mimicking the insect wings in a vertical take-off and landing (VTOL). To produce the same lift, the FWR’s flapping frequency, twist angle, and self-propelling rotational speed is significantly smaller than the insect-like flapping wings and rotors. Like its opponents, however, the effect of variant flapping frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…On the other hand, under the same input voltage, the FWR of PPAV in Cases 2 share the highest aerodynamic efficiency (over twice than that in Cases 1, Cases 3 and Cases 4). According to the previous studies [14], [25], optimal average twisting angle of the FWR should be 30° (as given in both Cases 2 and Cases 4) and thus the poor performance of Cases 4 is mainly due to its larger weight. The results demonstrated that a pair of lighter wings (Wing A) would have higher efficiency.…”
Section: The Effect Of Passive Pitching Angle On the Fwr Motion And Efficiencymentioning
confidence: 94%
See 4 more Smart Citations
“…On the other hand, under the same input voltage, the FWR of PPAV in Cases 2 share the highest aerodynamic efficiency (over twice than that in Cases 1, Cases 3 and Cases 4). According to the previous studies [14], [25], optimal average twisting angle of the FWR should be 30° (as given in both Cases 2 and Cases 4) and thus the poor performance of Cases 4 is mainly due to its larger weight. The results demonstrated that a pair of lighter wings (Wing A) would have higher efficiency.…”
Section: The Effect Of Passive Pitching Angle On the Fwr Motion And Efficiencymentioning
confidence: 94%
“…A measurement system was built to capture the kinematics of motion and measure the corresponding lift produced by the FWR. Assuming the FWR average rotary speed is constant [23]- [25], a trace line diagram of the FWR trailing edge during a flapping motion is illustrated in Figure 4. Wherein, the green line stands for the trace line of the wing with pitching angle variation while the red line for the wing of constant pitching angle (30°).…”
Section: B Setup Of Experimental Devicesmentioning
confidence: 99%
See 3 more Smart Citations